2019
DOI: 10.24925/turjaf.v7i3.405-416.2341
|View full text |Cite
|
Sign up to set email alerts
|

Farklı Yoğunluktaki Ses Dalgalarının Vakum Ambalajlanmış Hamsi (Engraulis encrasicolus) Marinatının Rengine ve Raf Ömrüne Etkisinin Belirlenmesi

Abstract: Suitability of marinated anchovies for ultra sound application as well as the effect of ultra sound on the shelf-life and color properties of marinated anchovies were investigated. In this regard, TVB-N, TBAR’s, pH, texture profile, water activity and color analyses were conducted on varying level of ultra sound (250 W/L, 500 W/L, 750 W/L for group A, B and C, respectively) applied vacuum-packaged marinated anchovies (Engraulis encrasicolus) during their shelf-lives. Based on the TVB-N results obtained, shelf-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
3
1
0
Order By: Relevance
“…However, the results of our study showed that the use of ultrasound increases the amount of TVB-N. Similar results were obtained from Ayvaz et al (2019). Researchers have reported that this is related to the easier breakdown of compounds found in muscles by the effect of cavitation.…”
Section: Results and Di̇scussi̇on Physicochemical Analysis Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…However, the results of our study showed that the use of ultrasound increases the amount of TVB-N. Similar results were obtained from Ayvaz et al (2019). Researchers have reported that this is related to the easier breakdown of compounds found in muscles by the effect of cavitation.…”
Section: Results and Di̇scussi̇on Physicochemical Analysis Resultssupporting
confidence: 91%
“…It was observed that the application of ultrasound had no effect on the water activity of sardine fish (P >0.05). Similar results were obtained from Ayvaz et al (2019) that applied ultrasound to marinated anchovy.…”
Section: Results and Di̇scussi̇on Physicochemical Analysis Resultssupporting
confidence: 81%
See 2 more Smart Citations